The role of knowledge in water service coproduction and policy implications. (December 2022) - Landriani, Loris; Agrifoglio, Rocco; Metallo, Concetta; Lepore, Luigi
Abstract: More than 50 years after the seminal studies of Elinor Ostrom, the concept of water service "coproduction" is of interest due to its ability to achieve a delicate balance of governance in the sector. This novel analysis applies a systematic literature review to the water coproduction policies to identify the factors that promote their successful development. The results show that knowledge is the decisive element for newly shared governance. From this study, implications for water management and research are derived. Highlights: More than 50 years, the theme of coproduction remains of considerable relevance. The literature has investigated three pillars of coproduction in public services: antecedents, management tools and outcomes. Knowledge is a fundamental "ingredient" of successful water coproduction. Water management requires a broader common vision. Knowledge management is a pillar of the new governance in water utilities.